Effect of Using Tasks Distribution Formats among Cooperative learing Groups for Aquiring Performance of some free style Wrestling holds - Hazim A. Matrood (مجلة الرافدين للعلوم الرياضية, 2013)
The study aimed at being acquainted with the effects of using tasks distribution formats among cooperative learning groups for acquiring performance of some free style wrestling holds. The Experimental method was used since it is convenient to the nature of the study. The society of the study included (143) students of the third stage of the sport education college , University of Mousl at academic year 2011-2012. The sample included (5) classes with 16 students each. The sample divided into four experimental groups. The First and Second groups used one of the tasks distribution format among cooperative learning groups for complete skill. The Third and fourth groups used one of the tasks distribution formats among cooperative learning groups for partial skill . The program for every group lasted (8) weeks with (2) learning sessions . The time of the learing session was (90) minutes. Standardized tests were adopted to achieve the study objectives . After concluding the tests and processing them statistically , the study concluded the following: 1-Teaching by using tasks distribution formats among cooperative learning groups had contributed in acquiring the performance of some free style wrestling holds. 2- The first Experimental group , used one of the tasks distributions formats among cooperative learning groups for complete skill, had proved an efficiency compared to the other experimental groups which used the partial skill for acquiring the performance of some free style wrestling catches. 3- The first Experimental group , used one of the tasks distributions formats among cooperative learning groups with Auto(loose) format of the skill, had proved an efficiency compared to the other experimental groups which used the directed (systematic) format of the skill to acquire the performance of some free style wrestling holds.